Leadership Styles for Leaders of Governmental Primary Schools and its Relationship with Effective Communication from Female Teachers’ standpoint in Jeddah Governorate - Alghamdi, Wafa Omar Ahmed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the relationship between leadership styles of government primary school leaders in Jeddah Governorate and its relationship with effective communication from the point of view of female teachers. A quantitative, descriptive, analytical approach and questionnaire were used as a study tool, distributed to a sample of (706) female teachers. The result of the study came as follows: The overall instrument obtained an average (3.71 out of 5), with a degree of approval (large) and at the level of styles, the (participatory) democratic styles obtained the highest average (4.03), followed by the autocratic (dictatorial) styles with an average of (3.78), both of which with a degree of practice (large), and finally the chaotic (permissive) style; Average (3.32) and degree of practice (medium). As for the styles of communication, Oral communication obtained the highest average (3.75 out of 5), followed by styles of communication through symbols, movements, and expressions with an average of (3.41), both with a degree of practice (large). It was also shown that there were no statistically significant differences between answers according to the variable of academic qualification, while I found that according to the variable of years of experience (more than 20 years) the average arithmetic higher than other categories of experience. Finally, the correlation coefficients between its were equal (0.814), which is a high positive value and statistically significant function. Based on the results, the researcher presented a set of recommendations, including: The necessity from the Ministry of Education to strengthening the practice of democratic (participatory) style in general education schools, and organizing more training courses and workshops to develop the skills of leaders in The field of participatory leadership, providing more opportunities for female teachers to express opinions and advice, such as participation in developing curricula and the school environment.